Barbaric splendour (Oxford)
viii, 139 sayfa
Keywords: “Barbaric Splendour : the use of image before and after Rome comprises a collection of essays comparing late Iron Age and Early Medieval art. Though this is an unconventional approach, there are obvious grounds for comparison. Images from both periods revel in complex compositions in which it is hard to distinguish figural elements from geometric patterns. Moreover, in both periods, images rarely stood alone and for their own sake. Instead, they decorated other forms of material culture, particularly items of personal adornment and weaponry. The key comparison, however, is the relationship of these images to those of Rome. Fundamentally, the book asks what making images meant on the fringe of an expanding or contracting empire, particularly as the art from both periods drew heavily from – but radically transformed – imperial imagery. This book comprises a collection of essays comparing late Iron Age and Early Medieval art. Fundamentally, the book asks what making images meant on the fringe of the expanding or contracting Roman empire, particularly as the art from both periods drew heavily from - but radically transformed - imperial imagery.” --